How does government efficiency affect carbon emission intensity? A comprehensive empirical study - Yemin, Ding; Lee, Chin; Taghizadeh-Hesary, Farhad; Abdul-Rahim, Abdul Samad; Peidong, Deng (Springer, 2023)
This study utilized panel data from 132 countries spanning from 1996 to 2019 to examine the effect of government efficiency on carbon emission intensity. Using a fixed effect model, the study found that stronger government efficiency is associated with a significant decrease in carbon emission intensity. Robustness tests were performed, the results of which consistently supported the main findings. Additionally, the study investigated the mechanisms underlying the linkage between government efficiency and carbon emission intensity, revealing that improved government efficiency can inhibit carbon emission intensity by fostering environmental innovation and promoting renewable energy consumption. Finally, the study examined the moderating effects of national income level, economic freedom, democracy, and ruling party ideology on the nexus of government efficiency and carbon emission intensity, and found empirical evidence supporting these moderating effects. These results provide new insights for governments seeking to reduce carbon emission intensity.